INFLUENCE OF METABOLIC SYNDROME ON DENTAL IMPLANTS HEALTH - Mihaela Doru-Butnaru; Dora-Maria Popescu; Dorin-Nicolae Gheorghe; Maria-Alexandra Martu; Luminita Lazar; Petra Surlin (Romanian Dental Association for Education, 2020)
The metabolic syndrome is a complex pathology, multisystemic, with numerous consequences that include: high blood sugar, hypertension, visceral obesity, dyslipidemia with high levels of triglycerides (TG) and low levels of HDL. Recent studies have published in the specialty literature, data that suggest the existence of a possible association between obesity and periimplantitis. The purpose of this report cases is to explore the possible relation between the metabolic syndrome and the development of periimplantitis. To reach the proposed objective we have evaluated the characteristics of periimplant tissues in patients that have a metabolic syndrome associated.